The value of total tumor diameter in unilateral multifocal papillary thyroid carcinoma: a propensity score matching analysis - Wu, Zhu-juan; Xia, Bao-ying; Chen, Zi-wei; Gong, Hao; Abuduwaili, Munire; Xing, Zhi-chao; Su, An-ping (Frontiers in Endocrinology, 2023)
Background Tumor multifocality is frequently observed in papillary thyroid carcinoma (PTC).However, the maximum tumor diameter (MTD), currently utilized in various staging schemes, might not accurately indicate the level of aggressiveness exhibited by multifocal tumors. We aimed to investigate the relationship between total tumor diameter (TTD) and clinicopathological features of papillary thyroid carcinoma.Retrospective data analysis was done on 1936 individuals who underwent complete thyroidectomy for PTC. Patients were classified into subgroups according to unilateral multifocality, central lymph node metastasis (CLNM) and lateral lymph node metastasis (LLNM).The relationships of clinicopathological features among these groups were analyzed.Unilateral multifocality was observed in 117 patients. The clinicopathological features of the unilateral multifocal PTC were similar to the unifocal PTC with approximate TTD. The unilateral multifocality played no independent role in CLNM and LLNM. Moreover, the efficiency of TTD in predicting CLNM and LLNM was significantly higher than that of MTD.In the case of unilateral multifocal PTC, TTD is a more accurate indicator of the biological characteristics of the tumor than MTD.